AN INVESTIGATION ON THE RELATIONSHIP BETWEEN THE FLOW STATE AND THE LEISURE BOREDOM OF HANG-GLIDING PILOTS - Özgür Tez; Pınar Güzel (ümit doğan üstün, 2019)
The purpose of this research was to investigate relationships between leisure boredom and flow experience in hang-gliding pilots according to the demografic variables. Sample group of the research consist of 314 ( female 59 =26.47 sd= 4.12 years; male 255 = 30.98 sd= 6.80) hang-gliding pilots from different categories (beginning, intermediate, pilot, experienced, instructor). The data collection tool used in the research consists of 3 sections. In the first section, a demographic questionnaire, in the second section "The Leisure Boredom Scale (BZSA) and the last section "The Dispositional Flow Scale Sort Form (DFS-2)" were used to data collection of hang-gliding pilots. Mann Whitney U, Kruskal Wallis H and Post-hoc Bonferonni tests were used in the evaluation of the data together with the descriptive statistics. As a result of analysis significant differences were in terms of flow experience according to gender, age, live pilot and income, participant level and frequency, educational status, institutional variables (p<.05); significant differences were in terms of leisure boredom according to gender, age, live pilot and income, participant level and frequency, educational status, institutional variables (p<.05).